Highlighting The Flaws In Admitted Patients Treatment Sheets In Cardiology Ward Of Federal Government Polyclinic Hospital: A Clinical Audit Report (Journal of Pharmaceutical Negative Results, 2023)
Objective The objective was to bring attention to the deficiencies identified by nurses, registrars, and consultants in the treatment documentation of the admitted patient. Our intervention had a positive impact on the medication administration record of in-patients, leading to improved patient care and better treatment outcomes. Negative reactions to medications or other consequences are experienced by hundreds of thousands of patients every year, yet many of them do not seek medical attention. Apart from the financial implications, medication errors inflict psychological and physical distress upon patients. A significant outcome of medication errors is the reduction in patient satisfaction and a consequent deterioration of trust in the healthcare system.